2020
DOI: 10.1055/s-0040-1716373
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Short-Term Complications in Smokers Undergoing Primary Unicompartmental Knee Arthroplasty

Abstract: The effects of smoking on unicompartmental knee arthroplasty (UKA) are unknown. The purpose of this study was to evaluate the effects of smoking on short-term outcomes following primary UKA. A query of the National Surgical Quality Improvement Project (NSQIP) database was used to identify cases of primary UKA performed during years 2006 to 2017. Patient demographics, operative times, and postoperative complications were compared between smoking and nonsmoking cohorts. Descriptive statistics, univariate analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Following an assessment of 2035 pertinent examinations, 15 tests released between 2003 and 2023 were included in the meta‐analysis since they matched the criteria for inclusion 6–20 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following an assessment of 2035 pertinent examinations, 15 tests released between 2003 and 2023 were included in the meta‐analysis since they matched the criteria for inclusion 6–20 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
“…inclusion. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Table 2 summarises the findings of these investigations. A total of 560 819 personals with PTH&TKA were in the used studies' starting point, 73 673 of them were smokers and 487 146 were non-smokers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…дольше, чем без нее. Однако не было обнаружено достоверных различий в частоте краткосрочных послеоперационных осложнений, частоте ревизионных вмешательств и среднем времени пребывания пациентов в стационаре между парциальной артропластикой с компьютерной навигацией и прецизионной хирургической техникой [44].…”
Section: Discussionunclassified
“…Although some studies have found improved complication rates with computer-assisted patellofemoral arthroplasty and unicompartmental knee arthroplasty (CA-UKA), others have found no difference. 1215 There are minimal data regarding outcomes of computer-assisted patellofemoral arthroplasty and computer-assisted bicompartmental knee arthroplasty (CA-BKA). 1618…”
mentioning
confidence: 99%